2023
DOI: 10.1021/jacs.3c01264
|View full text |Cite
|
Sign up to set email alerts
|

Triarylamine-Substituted Benzimidazoliums as Electron Donor–Acceptor Dyad-Type Photocatalysts for Reductive Organic Transformations

Abstract: Triarylamine-substituted benzimidazoliums (BI + − PhNAr 2 ), new electron donor−acceptor dyad molecules, were synthesized. Their photocatalytic properties for reductive organic transformations were explored using absorption and fluorescence spectroscopy, redox potential determinations, density functional theory calculations, transient absorption spectroscopy, and reduction reactions of selected substrates. The results show that irradiation of BI + −PhNAr 2 promotes photoinduced intramolecular electron transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…In a preliminary effort aimed at this goal, we found that 2-bromo-2-methyl- N -phenyl- N -phenylsulfonylpropaneamide undergoes the rearrangement to form 2-methyl-2-phenyl- N -phenyl-propaneamide when our originally developed organophotocatalysts, such as triarylamine-substituted benzimidazoliums (BI + –PhNAr 2 ), along with N , N -diisopropylethylamine (DIPEA) and acetic acid are used (above in Scheme 2 ). 8 In a recent investigation, we also developed processes in which BIH–R are employed to induce debrominative oxygenation reactions of α-bromoketones and -esters under an air atmosphere, at room temperature, and without light irradiation. 13 This observation suggests that the newly developed redox-based activation protocol would also be applicable to Truce–Smiles rearrangement reaction of 2-bromo- N -phenylsulfonylpropaneamides.…”
Section: Table 1 Desulfonylative Truce–smiles Rearrange...mentioning
confidence: 99%
See 3 more Smart Citations
“…In a preliminary effort aimed at this goal, we found that 2-bromo-2-methyl- N -phenyl- N -phenylsulfonylpropaneamide undergoes the rearrangement to form 2-methyl-2-phenyl- N -phenyl-propaneamide when our originally developed organophotocatalysts, such as triarylamine-substituted benzimidazoliums (BI + –PhNAr 2 ), along with N , N -diisopropylethylamine (DIPEA) and acetic acid are used (above in Scheme 2 ). 8 In a recent investigation, we also developed processes in which BIH–R are employed to induce debrominative oxygenation reactions of α-bromoketones and -esters under an air atmosphere, at room temperature, and without light irradiation. 13 This observation suggests that the newly developed redox-based activation protocol would also be applicable to Truce–Smiles rearrangement reaction of 2-bromo- N -phenylsulfonylpropaneamides.…”
Section: Table 1 Desulfonylative Truce–smiles Rearrange...mentioning
confidence: 99%
“…5 Our past studies of thermal as well as photochemical reactions involving BIH–R and BI + –R redox couples 4d k led to the development of a new series of BIH–R photoreductants 6 and BI + –R photocatalysts. 7 8 9…”
Section: Table 1 Desulfonylative Truce–smiles Rearrange...mentioning
confidence: 99%
See 2 more Smart Citations
“…[29] The same protocol was used for arenesulfonamides, but its application is limited by the use of high temperature and UV light. [30] A few reductive photodesulfonylation methods based on visible light photoredox catalysis have also been described; [31][32][33][34][35][36][37][38][39] recently, Budén, [40] Nicewicz, [41] Kang [42] and Hasegawa [43] published photodetosylation using an excited Hantzsch ester anion, an acridinium salt, diphenyldibenzocarbazole or triarylamine-substituted benzimidazolium, respectively (see example in Scheme 1B). However, all these photochemical methodologies suffer from limited substrate scope from the point of view of sulfonyl group structure and are limited to tosyl derivatives.…”
Section: Introductionmentioning
confidence: 99%